(untitled) (Journal of Intellectual Property Rights (JIPR), 2023)
The aim of the case study is to reflect on the FDA regulations on the Medical Devices, aspects of classifying the risk caused by the devices and to study the process of recalls by the companies strategically followed by the regulatory authority. Further, a case study was performed to identify the medical devices that were recalled in the year 2020, to investigate the reason for the recall, the subsequent effects on the system and further actions to rectify the problems. The study emphasized various reasons for the medical devices recalled during the year 2020. It warns the companies and users to follow the conditions strictly during their manufacture and trials which would minimize the errors of the functioning of the medical devices in the mere future. Also the study alerts the medical practitioners about the precautions and safe instructions to be followed during the installation and utilization of the devices.